Teaching English through Online Learning System during Covid-19 Pandemic - Tira Nur Fitria (Jurnal Pedagogy, 2020)
In the global Covid-19 pandemic, the Ministry of Education in Indonesia also issued a policy of closing schools and replacing the teaching and learning process by using an online learning system. This study aimed at investigating the online learning system in teaching English, which included the institution's support related to the online learning system and the lecturers' opinion in using the online learning system. This research method used descriptive qualitative. The subjects of this research were 81 English lecturers of some colleges or universities in Indonesia. The result showed that the institution's support in the online learning system could be described in three categories: (1) there were 66 respondents or 83.5 % said yes, (2) thee were 8 respondents or 10.1 % said no, and (3) there were 5 respondents or 6.5 % answer with other responses. Meanwhile, the English lecturers' opinion toward implementing an online learning system showed two responses between positive and negative responses. The 77 respondents or 97.5 %, said yes, then 2 respondents or 2.5 % said no to using the online learning system. In the teaching-learning process, the English lectures mostly used one online learning system, and some lectures used two or more online learning system. The 31 respondents or 40.3 % used Google Classroom, 6 respondents or 7.8 % used Zoom, 5 respondents or 6.5 % used Schoology, 5 respondents or 6.5 % used Edmodo, 4 respondents or 5.3 % used Moodle, as 2 respondents or 2.6 % used Google Meet, 2 respondents or 2.6 % used WhatsApp group. The other responses showed that they used self-platform, SPADA System, Elena Platform, UCY Learning, English Discoveries, Email, Skype, and BlogSpot. These results suggest that the online learning system has the potential to help the lecturers and students in the teaching and learning process.